Breaking walls. Democratic education: a communal project of citizenship - Teresa García Gómez (Revista Electrónica Interuniversitaria de Formación del Profesorado)
In this paper we define what we understand by democratic schools, which are pedagogical alternatives to the hegemony system of education. These alternatives are illustrated through several experiences which have taken place within and outside Spain. Although we acknowledge their importance and need to promote equality and justice, some limits to social transformation are pointed out as well as how to initiate the process of overcoming them.